2011
DOI: 10.1371/journal.pone.0026843
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Processing of Vibratory Communication Signals at the Level of Ascending Interneurons in Nezara viridula (Hemiptera: Pentatomidae)

Abstract: During mating, males and females of N. viridula (Heteroptera: Pentatomidae) produce sex- and species-specific calling and courtship substrate-borne vibratory signals, grouped into songs. Recognition and localization of these signals are fundamental for successful mating. The recognition is mainly based on the temporal pattern, i.e. the amplitude modulation, while the frequency spectrum of the signals usually only plays a minor role. We examined the temporal selectivity for vibratory signals in four types of as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Invertebrate duration selectivity for vibratory signals has also been found in ascending interneurons of insects (Zorović, 2011). Our results support the hypothesis that neural mechanisms of duration selectivity may be shared across vertebrates.…”
Section: Discussionsupporting
confidence: 85%
“…Invertebrate duration selectivity for vibratory signals has also been found in ascending interneurons of insects (Zorović, 2011). Our results support the hypothesis that neural mechanisms of duration selectivity may be shared across vertebrates.…”
Section: Discussionsupporting
confidence: 85%
“…Interneurons of one group are tuned to frequencies below 100 Hz, and those of the other to a broader frequency range, characteristic of the receptor neuron, responding best around 200 Hz. Zorović [109] confirmed that filtering of temporal characteristics of N. viridula vibratory communication signals occurs at the periphery of the species' central nervous system at the level of four different types of the ascending ventral cord neurons.…”
Section: -Sensory and Neuronal Systemmentioning
confidence: 78%
“…The repertory of stinkbug female rivalry interactions observed as synchronized signalling, exchange of different types of calling song signals and emission of the female rival song is more complex than the one reported for male/male stink bug interactions. In the latter interactions, males express rivalry only by exchanging of rival song pulses in a-b-a-b sequence (Čokl et al 2000, 2011Blassioli-Moraes et al 2005;Bagwell et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Songs have been determined according to the mating behavioral context as calling, courtship, copulatory, repelling and rival songs. The latter were identified and described only for males competing to copulate with the same female (Čokl et al 2000, 2011Blassioli-Moraes et al 2005;Bagwell et al 2008).…”
Section: Introductionmentioning
confidence: 99%